United Kingdom : 2003 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Kingdom. (IMF Staff Country Reports; Country Report ;, 2004)
The United Kingdom (U.K.) economy has weathered the global slowdown well, supported by an countercyclical monetary policy and an expansionary fiscal stance. Executive Directors welcomed this developments, and stressed the need to tighten monetary, fiscal, and macroeconomic policies. They commended the trade liberalization, the Common Agricultural Policy, the financial system, and the efforts in combating money laundering and terrorism financing. They encouraged the authorities to reintroduce momentum in the Doha round negotiations, and to increase the effective access of the least-developed countries to industrial country markets.